Deciphering the Transcriptional-Regulatory Network of Flocculation in Schizosaccharomyces pombe - Kwon, Eun-Joo Gina (Public Library of Science, 2012)

(untitled)
In the fission yeast Schizosaccharomyces pombe, the transcriptional-regulatory network that governs flocculation remains poorly understood. Here, we systematically screened an array of transcription factor deletion and overexpression strains for flocculation and performed microarray expression profiling and ChIP–chip analysis to identify the flocculin target genes. We identified five transcription factors that displayed novel roles in the activation or inhibition of flocculation (Rfl1, Adn2, Adn3, Sre2, and Yox1), in addition to the previously-known Mbx2, Cbf11, and Cbf12 regulators. Overexpression of mbx2(+) and deletion of rfl1(+) resulted in strong flocculation and transcriptional upregulation of gsf2 (+)/pfl1(+) and several other putative flocculin genes (pfl2(+)–pfl9(+)). Overexpression of the pfl(+) genes singly was sufficient to trigger flocculation, and enhanced flocculation was observed in several combinations of double pfl(+) overexpression. Among the pfl1(+) genes, only loss of gsf2(+) abrogated the flocculent phenotype of all the transcription factor mutants and prevented flocculation when cells were grown in inducing medium containing glycerol and ethanol as the carbon source, thereby indicating that Gsf2 is the dominant flocculin. In contrast, the mild flocculation of adn2(+) or adn3(+) overexpression was likely mediated by the transcriptional activation of cell wall–remodeling genes including gas2(+), psu1(+), and SPAC4H3.03c. We also discovered that Mbx2 and Cbf12 displayed transcriptional autoregulation, and Rfl1 repressed gsf2(+) expression in an inhibitory feed-forward loop involving mbx2(+). These results reveal that flocculation in S. pombe is regulated by a complex network of multiple transcription factors and target genes encoding flocculins and cell wall–remodeling enzymes. Moreover, comparisons between the flocculation transcriptional-regulatory networks of Saccharomyces cerevisiae and S. pombe indicate substantial rewiring of transcription factors and cis-regulatory sequences.